A Low Cost Carbon Nanofiber Based Spiral Inductor: Inference and Implementation - John Wiselin; Sreeja Balakrishnapillai Suseela; Bycil Viswambaran Jalaja; Sherin Dhas Sahayadas Padma Ramani; Rajesh Prasad; Sheeba Devaraj; Suhaila Shahul; Sowmya Swaminathan (Advances in Materials Science and Engineering)
This paper investigates the possibilities of using carbon fiber as an inductor material by analyzing its inductive properties. Various shapes such as rectangular, spiral, helical, and cylindrical line structures have been simulated under various constraints using simulation software. Hardware implementations were also tested and both simulation and hardware results show that carbon fibers have the potential to replace copper inductor lines. The implemented spiral inductor produced a quality factor of 40 while producing an inductance of 4 nH at 1.2 GHz frequency.